2002
DOI: 10.1073/pnas.142409899
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the cell cycle and maize transformation by disruption of the plant retinoblastoma pathway

Abstract: The genome of the Mastreviruses encodes a replication-associated protein (RepA) that interacts with members of the plant retinoblastoma-related protein family, which are putative cell cycle regulators. Expression of ZmRb1, a maize retinoblastoma-related gene, and RepA inhibited and stimulated, respectively, cell division in tobacco cell cultures. The effect of RepA was mitigated by over-expression of ZmRb1. RepA increased transformation frequency and callus growth rate of high type II maize germplasm. RepA-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
78
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 74 publications
6
78
0
Order By: Relevance
“…To determine whether overexpression of Zeama;KRP;1 and Zeama;KRP;2 can cause endoreduplication in cells in which the activity of the maize RBR is reduced or eliminated, embryonic calli were transformed with gene constructs expressing the wheat dwarf virus RepA protein in the presence and absence of the maize KRPs. RepA was previously shown to interact with the maize RBR protein and stimulate the cell cycle (Grafi et al, 1996;Gordon-Kamm et al, 2002). Maize embryos were transformed by particle bombardment as described by Gordon-Kamm et al (2002), and, after culturing them on selective media, the levels of Zeama;KRPs and RepA transcripts were measured by RT-PCR and the nuclear ploidy of cells was determined by flow cytometric analysis.…”
Section: Ectopic Expression Of Zeama;krp;1 Can Induce Endoreduplicatimentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether overexpression of Zeama;KRP;1 and Zeama;KRP;2 can cause endoreduplication in cells in which the activity of the maize RBR is reduced or eliminated, embryonic calli were transformed with gene constructs expressing the wheat dwarf virus RepA protein in the presence and absence of the maize KRPs. RepA was previously shown to interact with the maize RBR protein and stimulate the cell cycle (Grafi et al, 1996;Gordon-Kamm et al, 2002). Maize embryos were transformed by particle bombardment as described by Gordon-Kamm et al (2002), and, after culturing them on selective media, the levels of Zeama;KRPs and RepA transcripts were measured by RT-PCR and the nuclear ploidy of cells was determined by flow cytometric analysis.…”
Section: Ectopic Expression Of Zeama;krp;1 Can Induce Endoreduplicatimentioning
confidence: 99%
“…Although Zeama;KRP;1 was found to be associated with the CKI activity described by Grafi and Larkins (1995), it did not account for all of the CDK inhibitory activity present in this fraction. Overexpression of Zeama;KRP;1 in maize embryonic calli that ectopically expressed the wheat dwarf virus RepA protein, which counteracts Rb-related (RBR) protein function (Grafi et al, 1996;Gordon-Kamm et al, 2002), led to an additional round of DNA replication without nuclear division. While a clear role for Zeama;KRP;1 in endoreduplication could not be demonstrated in maize endosperm, indirect evidence suggests this protein could be involved in this process.…”
mentioning
confidence: 99%
“…At least two of their proteins, Rep and RepA, repress the plant cell RBR and, thus, activate the replication machinery required to amplify the viral genome [14]. In tobacco cells, constitutive expression of the viral RepA protein induced cell division and conferred a high-competence transformation phenotype, whereas RepA expression in maize resulted in calli that remained embryogenic and were readily regenerable, suggesting that RepA was able to overcome the G0-G1 blockage [36].…”
Section: Esr1mentioning
confidence: 99%
“…Thus far, RBR inactivation has been reported in plant species with apparently a single RBR gene, such as Arabidopsis 14 and Nicotiana, 15 or in maize undifferentiated cells. 11 It would be interesting to know whether a differential response of naive and differentiated/senescent cells to the loss of function of one pocket protein, similar to that identified in mammals, is also true for plants, such as maize, with a complex and interdependent RBR family of proteins. The study of the regulation of the RBR-E2F pathway in terminally differentiated endosperm cells might provide important insights concerning this question.…”
mentioning
confidence: 99%
“…Competence for proliferation is an important prerequisite for the genetic transformation of plant cells. 11 It has been shown that sucrose and hormone concentrations in tissue culture medium are perceived by CycD3;1/CDK in Arabidopsis, which are upregulated. 12 In tobacco cell culture, upregulation of CycD3;1 stimulates cell proliferation by the direct inhibition of RBR.…”
mentioning
confidence: 99%